Focal Segmental Glomerulosclerosis caused by Hepatitis B Infection Comorbid with HIV Infection - Nicholas Wijayanto; Yenny Kandarini; IDN Wibawa; Ni Wayan Winarti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Glomerulonephritis is an inflammatory condition on renal glomerulus. These entities can manifest as nephrotic syndrome. One of causes of secondary glomerulonephritis is hepatitis B infection. Glomerulonephritis due to hepatitis B only happens in 0.1 – 25% cases, with the focal segmental glomerulosclerosis (FSGS) is rarely reported. We reported 20 years old male with nephrotic syndrome. He was homosexual with history of unprotected sex and multiple partners. From kidney biopsy, we found focal segmental glomerulosclerosis lesion. Blood examination showed he had both hepatitis B (HBV-DNA 1.7x108 IU/mL) and HIV infection (HIV-RNA 820 copies/mL, CD4 839 cell/uL). We treated this patient with combination of anti-viral drugs which consist of tenofovir, lamivudine and efavirenz. After three weeks of treatment, he showed improvement in the clinical symptoms and urinalysis.